Board Game sebagai Media Menurunkan Stres pada Remaja Akhir (18-22 Tahun) - Wardhani, Ayu Kusuma; Pujiyanto, Pujiyanto; Pahlevi, Andreas Syah (Universitas Negeri Malang, 2024)
Board Game is a game that is played in groups, in one game there are at least 2 to 3 people therefore board games are very closely related to social interaction. Interacting with other people is one way to reduce stress, as is the purpose of the Story on Party board game which is to reduce stress in late teens who are in transition. In this design the author uses the Bruce Archer method. The stages start from programming, data collection, analysis, synthesis, development, and communication. The result of this design is a set of Story on Party board games consisting of boards, cards, supply coins, heart coins, pawns, dice, coupons, playing guide books, and board game packaging. In addition, there are also supporting media in the form of posting promotional content on the official Instagram account of the Story on Party board game which aims to introduce this board game using the microblog method. Board game merupakan permainan yang dimainkan secara berkelompok, biasanya melibatkan minimal 2 hingga 3 orang, sehingga sangat erat kaitannya dengan interaksi sosial. Berinteraksi dengan orang lain adalah salah satu cara efektif untuk mengurangi stres. Hal ini sejalan dengan tujuan dibuatnya board game